Pelatihan Pembuatan Olahan Dasar Saripati Bayam menjadi Masakan Khas Aceh di Desa Curug Wetan - Yuliantoro, Nonot; Juliana; Hassan, Rayyani; Stefany; Alfenny, Verellyn (Jurnal Abdimas Pariwisata, 2024)
Training on Making Basic Spinach Extract into Acehnese Specialty Dish in Curug Wetan Village Aceh Province is one of the provinces that has a variety of very distinctive dishes, such as: Mie Aceh dan Roti Canai.  Spinach essence is one of the innovations made in making basic preparations for Aceh Noodles dan Roti Canai,. This innovative product is made as attractive as possible and as complete as possible so that later it can be useful among the wider community. Training on making basic processed spinach essence into aceh cuisine in the village of Curug Wetan was carried out with the hope of providing the latest innovations that will be useful in the future for opening an independent business. The implementation is carried out face-to-face and workshops and events are also equipped with pre-tests and post-tests to measure the understanding of Pkk mothers who attend this training event. Because the significance value is less than 0.05, it proves that the comparison is valid. So, it is hoped that there will be a continuation of this training activity so that Pkk mothers can practice it directly both at home and as a resource to open an independent business.